The Antimicrobial and Host Defense Peptides of Drosophila melanogaster. - Hanson, M.A.; Westlake, H.E.; Bulet, P.; Lemaitre, B. (Annual Review of Microbiology, 2025)
Drosophila fruit flies are a powerful model for studying innate immunity. In Drosophila, seven classical antimicrobial peptide (AMP) gene families were identified in the 1990s. These genes are primarily regulated by the TOLL and IMD NF-?B pathways in response to infection. Analyses of mutants have revealed their important roles, including a surprising degree of peptide-microbe specificity at the effector level, in the host defense against gram-negative bacteria and fungi. Many new families of host defense peptides (HDPs) with unknown mechanisms of action are now being investigated. One prominent example is the Bomanins, which are peptides with an essential role in combatting infection by practically all gram-positive bacteria and fungi. Recent studies suggest that AMPs may have broader roles beyond direct antimicrobial activity, notably in the brain and behavior. This review summarizes what is known about each family of Drosophila HDPs and provides supplementary discussion for less characterized genes involved in defense against infection.